2014
DOI: 10.5152/balkanmedj.2014.13218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Tests Using Information Theory for Multi-Class Diagnostic Problems and its Application for the Detection of Occlusal Caries Lesions

Abstract: Diagnostic tests are widely used in medical science for diagnosing the presence or absence of a disease. These tests may not discriminate between subjects with and without the disease or disorder with perfect accuracy. Several methods are available to evaluate the performance of diagnostic tests when the purpose of the test is to discriminate between two possible disease states. Different performance indices have been proposed to determine the accuracy of diagnostic tests when both the disease state and the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…4,7,10,21 Overall, results from the included studies showed micro-CT as accurate as histology for diagnose caries lesion from sound tissue and for depth of caries lesion. 3,[6][7][8][9][10][11]21,22 However, in some studies micro-CT was not accurate to assess enamel lesions, 5 did not classify adequately the depth of the lesion 12 and showed moderate agreement with histology for enamel caries detection. 4…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…4,7,10,21 Overall, results from the included studies showed micro-CT as accurate as histology for diagnose caries lesion from sound tissue and for depth of caries lesion. 3,[6][7][8][9][10][11]21,22 However, in some studies micro-CT was not accurate to assess enamel lesions, 5 did not classify adequately the depth of the lesion 12 and showed moderate agreement with histology for enamel caries detection. 4…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…The search identified 270 records and after removing duplication, 187 remained being selected to full-text analysis. In total, 12 studies were selected [3][4][5][6][7][8][9][10][11][12]21,22 and from these, three studies 4,10,11 were retained to meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…While IT tools have widely been suggested in medical statistics and diagnostics (e.g. see [ 4 , 5 , 8 10 , 35 – 37 , 46 , 47 ]), they have not been used as broadly in relation with agreement measures. On this research track, we can only mention [ 31 ], where a normalised weighted MI is used as an index of intercoder agreement , and [ 29 ], which uses MI to quantify the information shared between outcomes of multiple healthcare surveys.…”
Section: Introductionmentioning
confidence: 99%